Patient and lesion characteristics in late/very late stent thrombosis with everolimus-eluting stents from real-world adverse event reporting. Issue 3 (March 2020) - Konishi, Akihide; Mitsutake, Yoshiaki; Ho, Mami; Handa, Nobuhiro; Koike, Kazuhisa; Mochizuki, Shuichi; Ishii, Kensuke
Highlights: A total of 370 patients with definite stent thrombosis (ST) after everolimus-eluting stent implantation were analyzed. These patients were divided into early (E)ST group and late (L)ST/very late (VL)ST group. Restenosis and hemodialysis were significantly higher in LST/VLST than EST. The in-hospital death rate was comparable between two groups. Abstract: Background: Stent thrombosis (ST) is a rare but serious complication after deployment of a drug-eluting stent. The features of ST after implantation of an everolimus-eluting stent (EES) have not been fully elucidated. Methods: A comprehensive survey of real-world adverse event reporting with conditions for approval under the Pharmaceuticals and Medical Devices Act identified 490 cases of ST with EES. A total of 370 patients with definite ST after EES implantation [287 with early (E)ST (within 30 days), 54 with late (L)ST (31–365 days), and 29 with very late (VL)ST (over 1 year)] were divided into an EST group and an LST/VLST group to compare the patients and lesions characteristics. Results: The frequency of patients with hemodialysis and in-stent restenosis (ISR) lesions were significantly higher in the LST/VLST group than in the EST group (hemodialysis, 22.9% vs 2.7%, p  = 0.0001; ISR lesions, 25.9% vs 9.4%, p  = 0.0001). Characteristic demographic factors for LST/VLST versus EST identified by multivariable model were hemodialysis and ISR lesions (hemodialysis: odds ratio 7.348, 95% confidence interval 2.458–21.968, p  = 0.0001; ISR lesions: odds ratio, 2.490, 95% confidence interval 1.100–5.638, p  = 0.027). The in-hospital death rates from ST were not significantly different between the EST group and the LST/VLST group (EST, 15% vs LST/VLST, 21.7%, p  = 0.147). Conclusions: Patient-related and lesion-related characteristics were significantly different between EST and LST/VLST. Data collection from adverse event reporting could be a helpful strategy for evaluation of this serious but rare complication.